DESCRIPTIVE GEOMETRY IS THE BASIS OF TECHNICAL DEVELOPMENT OF STUDENTS OF OP E4 "EARTH SCIENCE" - Василишин, Віталій (SWorldJournal, 2025)
The article is devoted to the importance of descriptive geometry as a fundamental discipline in the technical training of students of the educational program E4 "Earth Sciences". The author explores the role of descriptive geometry in the formation of spa